Rupestrisine A and B, two novel dimeric indole alkaloids from Alstonia rupestris. (21st December 2021) - Wang, Zhi-Wei; Zhang, Jin-Ping; Wei, Quan-Hao; Chen, Long; Lin, Yun-Liang; Wang, Yu-Liang; An, Tao; Wang, Xiao-Jing
Graphical abstract: Highlights: Two novel bisindole alkaloids were isolated from Alstonia rupestris . The absolute configurations of 1 and 2 were established. Compound 1 showed moderate anti-inflammatory activity. Abstract: Rupestrisine A (1 ), an unprecedented heteroyohimbine-kopsinine type dimeric indole alkaloid, and rupestrisine B (2 ), the first example of yohimbine-kopsinine type bisindole alkaloid, were isolated from Alstonia rupestris . Their structures were elucidated based on 1D and 2D-NMR, MS, ECD, FTIR and UV spectroscopic data. Compound 1 showed moderate activity of inhibiting NO production of RAW264.7 cells induced by lipopolysaccharide with an IC50 value of 17.5 ± 1.6 μM.